Triumph of Good Will : How Terry Sanford Beat a Champion of Segregation and Reshaped the South - Drescher, John, 1960- (Book collections on Project MUSE., 2000)
"Both Terry Sanford and I. Beverly Lake were Democrats in the one-party South of that era. Yet they were different in almost every other way. Lake, a middle-aged law professor, was committed to segregation. Sanford, an ambitious young politician and lawyer, believed in expanding opportunities for all citizens. Their race was a heated struggle that would bind them together for the rest of their lives." "With unparalleled access to both sides and with an objective correspondent's hindsight view, John Drescher has written the story of a campaign that set the winning strategy for many who followed, and the biography of a winning candidate, a governor rated as one of the finest of the twentieth century."--Jacket